2013
DOI: 10.1016/j.jpeds.2013.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin Prophylaxis to Prevent Intraventricular Hemorrhage: Association between Incidence and Timing of Drug Administration

Abstract: Objective To test the hypothesis that administration of indomethacin prophylaxis before 6 hours of life results in a lower incidence of intraventricular hemorrhage (IVH) compared with administration after 6 hours of life, and that the effects of early prophylaxis depend on gestational age (GA) and sex in very low birth weight infants (birth weight <1250 g). Study design Very low birth weight infants admitted to our neonatal intensive care unit between 2003 and 2010 who received indomethacin prophylaxis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 29 publications
(30 reference statements)
0
8
1
1
Order By: Relevance
“…(11) Data available from the NICHD Neonatal Research Network Generic Database provided the opportunity to examine the time of administration of indomethacin in a larger cohort derived from multiple centers. We confirmed that indomethacin prophylaxis before 6 hours of age does not decrease the incidence of IVH or death compared to later administration up to 24 h of age.…”
Section: Discussionmentioning
confidence: 99%
“…(11) Data available from the NICHD Neonatal Research Network Generic Database provided the opportunity to examine the time of administration of indomethacin in a larger cohort derived from multiple centers. We confirmed that indomethacin prophylaxis before 6 hours of age does not decrease the incidence of IVH or death compared to later administration up to 24 h of age.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the present study may have overestimated the number of PDA patients because indomethacin is also used to prevent IVH in premature infants. 21 In conclusion, there were no significant differences in mortality due to preterm PDA according to hospital volume. Surgical and medical treatment methods had a similar mortality, and there was no evidence to support the necessity for centralization of institutions treating PDA, at least in Japan.…”
Section: Discussionmentioning
confidence: 76%
“…Second, the diagnoses that are recoded in administrative claims databases are generally less well validated than those in prospective studies. Finally, the present study may have overestimated the number of PDA patients because indomethacin is also used to prevent IVH in premature infants …”
Section: Discussionmentioning
confidence: 85%
“…Thus, IVH in these infants has been attributed to changes in CBF in the periventricular germinal matrix, due to the particular structure of the matrix and micro vessels immaturity 10 . Indomethacin administration during the first day of life has been proven as an effective measure to prevent IVH, particularly severe grades 12 , 42 44 . Thus, indomethacin may reduce the hyperemic response favouring cerebral autoregulation 28 , 32 , 33 , promoting microvascular maturation in the germinal matrix 32 , 36 , 41 , and inhibiting changes in BBB permeability 28 .…”
Section: Discussionmentioning
confidence: 99%